Doubly Dynamic Self‐Healing Materials Based on Oxime Click Chemistry and Boronic Acids - Collins, Joe; Nadgorny, Milena; Xiao, Zeyun; Connal, Luke A. (Macromolecular rapid communications., 2017)
The dynamic covalent characteristics of oxime and boronate ester bonds have been explored. A small excess of a competing aldehyde under acidic conditions resulted in oxime polymer degradation from high molecular weights (30 kDa) to low molecular weight oligomers (2.2 kDa). The dynamic nature of oxime bonds imparts oxime cross‐linked hydrogels with self‐healing properties and the incorporation of phenyl boronic acid groups into the hydrogel network provides a platform for hydrogel functionalization. The addition of a polyphenol (tannic acid) proves a facile means to incorporate a second, dynamic covalent cross‐linking network through boronate ester formation which, owing to the increase in the degree of cross‐linking, is found to be nearly double the hydrogel strength (storage modulus increased from 4.6 to 8.5 kPa). Finally, the tannic acid cross‐linking network is selectively degraded returning the hydrogel storage modulus to its initial value and providing a means for the synthesis of materials with tunable mechanical properties. The dynamic covalent characteristics of the oxime bond have been explored. Through equilibrium manipulation, polymer degradation and hydrogel self‐healing are achieved. By exploiting the orthogonal nature of the oxime ligation, doubly dynamic hydrogels incorporating a boronate ester–tannic acid cross‐linking network are produced creating materials with tunable mechanical properties.